PENGARUH MODEL PEMBELAJARAN INKUIRI BERBASIS GREEN SCHOOL TERHADAP KEMAMPUAN LITERASI SAINS SISWA - Wida Herlina; Topik Hidayat; Taufik Rahman (Postgraduate, University of Mataram, 2022)
A Green School is an environmentally friendly educational program designed in such a way as to create a meaningful learning experience. learning environment contributes to the development of students' scientific literacy skills. The involvement of students in nature or environmental-based learning can increase students' sensitivity to the relationship between humans and the environment. Therefore, Green School was chosen as a way to teach environmental material. Using the Pre-post Experimental Group Design research design that was applied to SMPN students on the interaction of living things, the results showed that students who learned to use the Green School-based inquiry model experienced a significant increase in their scientific literacy skills. It is hoped that there will be further research on environmental learning using Green School-based inquiry, so that references can be obtained in developing students' scientific literacy skills in the future.